Adsorção de ciprofloxacina por carvão ativado produzido a partir de escama de peixe - Alberti, Schaline Winck (2022)
The indiscriminate use of antibiotics and the disposal of their waste without effective treatment have made drugs emerging pollutants, as they are complex molecules and difficult to degrade, causing harmful effects to the environment, and consequently to the population (even at low concentrations). Most conventional treatment techniques for domestic and industrial effluents are not efficient in eliminating persistent contaminants such as pharmaceuticals. Several advanced treatments can be used for the mitigation of these types of pollutants, among them, the adsorption has potential, especially considering its ability to treat pollutants at low concentrations, typically found for these substances in the environment. In this sense, with the development of this work, the objective was to study the removal of Ciprofloxacin (CIP) from aqueous solutions by the adsorption process using activated carbon (AC). Initially the adsorbent material was produced from fish scales, called: activated carbon of fish scale and activation with metallic salt (CAES) and activated carbon with pre-carbonized fish scale (CAEP). After the production of activated carbons, batch tests were performed to evaluate the adsorption capacity of Ciprofloxacin (CIP) at different pH values: 4, 7.5 and 10. From these results the CAEP adsorbent was selected to perform a more detailed study. Kinetic experiments were performed (pH 8, 24 h, 100 and 200 mg L-1 and 30°C) and then the models of pseudo-first order, pseudo-second order, pseudo-first order with two sites and pore diffusion were adjusted, and the last two described the process. The adsorption equilibrium - 10 different concentrations from 15 to 200 mg L-1, pH 7 to 10, 30 °C, 48 h and 250 rpm- (Langmuir, Freundlich, Jovanovic, Jovanovic with two sites, Langmuir with two sites, Langmuir Sigmoidal and BET) in which from the isotherm fits a maximum adsorption capacity of 92.51 mg g-1 at pH 7, with the Jovanovic with two sites isotherm characterizing the adsorption process, representing the behavior of the relationship between the equilibrium concentrations in the liquid and solid phases. Adsorption tests were performed on a fixed bed column (30°C, pH 8, flow rate ~4,6 mL min-1, column height ~10.,5 cm, adsorbent mass 2.5 g, at concentrations of 120, 80 and 40 mg L-1) obtaining a saturation capacity of 40.12 mg g-1 at the highest concentration and using Klinkenberg's model to model the breakthrough curves. Furthermore the characterizations of the activated carbon: Scanning electron microscopy - SEM, fourrier transform infrared spectroscopy - FTIR, X-ray diffraction (XRD), N2 physisorption, pycnometry, particle size distribution and adsorption test of the different CAEP phases aided in understanding the behavior of the experimental data, showing an activated carbon with two phases of different compositions, several functional groups, an irregular surface carbon of moderate porosity, a more amorphous material but with the presence of crystallinity, considerable surface area and mesoporous, with uniform particle size distribution and favorable size for mass transfer. Finally, it is concluded that CAEP is efficient in the removal of ciprofloxacin in batch system and presenting an average efficiency in fixed bed column of 46% and can be better adapted in future works.